Accessibility of The Kelapa-Seribu Islands Community to Health Service Facilities - Fakhirah, Jehan; Andita, Eurika Putri (UI Scholars Hub, 2023)
Background: Disparity in access to rural-urban health services is a global health priority problem. The health extension program is a basic preventive, promotive, and curative service targeting households to improve family health status with effective implementation, especially on remote islands. Therefore, we conducted this study to assess the utilization of health education programs and related factors in Kelapa Island, Pulau Seribu. Aims: This study aims to assess the utilization of health education programs and their factors in Kelapa-Seribu Islands. Methods: A mixed cross-sectional study at the household level in Kelapa-Seribu Islands. A multistage sampling procedure was used to select the 366 informants in this study. Researchers used SPSS software for data analysis. Results: The results showed that 54 (14.75%) informants had used the health education program. Residential health education package [Adjusted Odds Ratio/AOR: 3.438 (95% Confidence Interval/CI: 1.88, 6.33)], post-visit health [AOR: 1.73 (95% CI: 1.105, 2.685)], knowledge [AOR: 1.52 (95% CI: 1.043, 2.40), home visits by health educators [AOR: 1.57 (95% CI: 1.02, 2.630)], and graduation from model family training [AOR: 2.10 (95% CI: 1.27, 3.11)] are significant factors on the utilization of extension health services. Conclusion: The coverage of utilization of health education services in Kelapa Island is still low. Knowledge related to information on health education programs, residence, post-health visits, home visits, and family planning training is a significant factor in the utilization of health education services.